2018
DOI: 10.1097/hs9.0000000000000054
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 Inhibition Prolongs Survival in Mouse Models of MPN by Selectively Targeting the Disease Clone

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 55 publications
1
60
0
Order By: Relevance
“…32,86 One promising agent is the orally available LSD1 inhibitor IMG-7289 (bomedemstat) that had shown promising effects in animal models and is currently being tested in a phase I/II study in myelofibrosis patients intolerant of or refractory to ruxolitinib (NCT03136185). 87,88 Preliminary results from this trial showed an SVR in 50% of patients (not defined as ≥35% as in other trials) and ≥50% symptom reduction in 21% of patients. 88 However, it remains to be seen what the final results using more stringent response criteria show before the role of IMG-7289 in the treatment landscape of myelofibrosis can be evaluated.…”
Section: Discussionmentioning
confidence: 75%
“…32,86 One promising agent is the orally available LSD1 inhibitor IMG-7289 (bomedemstat) that had shown promising effects in animal models and is currently being tested in a phase I/II study in myelofibrosis patients intolerant of or refractory to ruxolitinib (NCT03136185). 87,88 Preliminary results from this trial showed an SVR in 50% of patients (not defined as ≥35% as in other trials) and ≥50% symptom reduction in 21% of patients. 88 However, it remains to be seen what the final results using more stringent response criteria show before the role of IMG-7289 in the treatment landscape of myelofibrosis can be evaluated.…”
Section: Discussionmentioning
confidence: 75%
“…This phase 2 study of IMG in myelofibrosis is continuing to accrue, and a second phase 2 trial to assess efficacy in patients with essential thrombocytosis has also recently opened. In a preclinical model of MPN, synergistic effects were seen with the combination of IMG, with commercially available JAK inhibitor, ruxolitinib, supporting further clinical evaluation of this combination strategy in future MPN patients [32].…”
Section: Expert Opinionmentioning
confidence: 74%
“…In the laboratory, LSD1 inhibition in mouse models of JAK2 mutant MPN significantly enhanced peripheral count, decreased splenomegaly, and reduced inflammatory cytokine levels as well as bone marrow fibrosis consistent with disease control. In addition, a reduction in the allelic burden of mutant JAK2V16F and significantly improved overall survival were observed [32]. Results of a recent phase I/2a study of IMG in patients with high risk or intermediate 2 risk myelofibrosis (MF) confirmed that this drug was well tolerated with only one patient developing a significant adverse effect related to IMG (painful splenomegaly).…”
Section: Expert Opinionmentioning
confidence: 95%
See 1 more Smart Citation
“…Third, bomedemstat (IMG-7289), an inhibitor of LSD1, an enzyme essential for platelet formation ( 86 ), was recently granted FDA fast-track designation for the treatment of ET patients (NCT04254978). In murine models of MPN, IMG-7289 has shown efficacy in reducing inflammation, splenomegaly and fibrosis, in addition to prolonged survival ( 87 ). IMG-7289 killed Jak2 V617F -mutant cells selectively and synergized with Jak inhibition in pre-clinical MPN mouse models ( 87 ).…”
Section: Therapeutic Targeting Of Soluble Mediators the Malignant Bomentioning
confidence: 99%